Utilization of fluoroquinolones and Escherichia coli resistance in urinary tract infection: inpatients and outpatients - Urbánek, Karel; Kolár, Milan; Strojil, Jan; Koukalová, Dagmar; Cekanová, Luboslava; Hejnar, Petr (Pharmacoepidemiology and drug safety, 2005)
OBJECTIVES: The aim of this study was to evaluate the dependence of Escherichia coli resistance to fluoroquinolones on their use in the outpatients and inpatients in the Olomouc region of the Czech Republic. METHODS: Data on inpatient antibiotic use were obtained from the database of the Department of Pharmacology and expressed as defined daily dose per 100 bed-days (DBD). Data on outpatient prescriptions were obtained from the database of General Health Insurance Company and expressed in defined daily doses per 1000 clients per day (DID). Escherichia coli strains were isolated from samples of urine of both community and hospitalized patients suffering from acute bacterial urinary tract infection, examined using aerobic cultivation, and determined by standard biochemical procedures. RESULTS: The utilization of fluoroquinolones in inpatients has significantly (p < 0.01) increased from 2.52 DBD in 1997 to 4.29 DBD in 2002. In outpatients, fluoroquinolone utilization has also increased significantly from 0.14 to 0.95 DID (p < 0.01). In the same period, 9192 E. coli strains were isolated from inpatients and outpatients suffering by urinary tract infections and tested for the susceptibility to fluoroquinolones. Resistance increased significantly (p < 0.01) both in the hospital (from 2 to 9%) and in the community (from 1 to 10%). The development of E. coli resistance to fluoroquinolones correlates significantly with their utilization both in the hospital (r = 0.944, p = 0.005) and in the community (r = 0.859, p = 0.029). CONCLUSIONS: Results of this study shows the impact of fluoroquinolone utilization on E. coli resistance and support the need of controlled use of these effective antibiotics.
Keywords: antiinfekční látky močové; infekce vyvolané Escherichia coli; Escherichia coli Infections; Humans; infekce močového ústrojí; Outpatients; Fluoroquinolones; Escherichia coli; lidé; spotřeba léčiv; nemocnice fakultní; Anti-Infective Agents, Urinary; Inpatients; Retrospective Studies; Drug Resistance, Bacterial; pacienti ambulantní; hospitalizovaní pacienti; Hospitals, Teaching; Czech Republic; bakteriální léková rezistence; retrospektivní studie; fluorochinolony; Drug Utilization; Urinary Tract Infections; Česká republika